Induction of Fear Extinction with Hippocampal-Infralimbic BDNF - Peters, Jamie (2010)
The extinction of conditioned fear memories requires plasticity in the infralimbic medial prefrontal cortex (IL mPFC), but little is known about the molecular mechanisms involved. Brain-derived neurotrophic factor (BDNF) is a key mediator of synaptic plasticity in multiple brain areas. In rats subjected to auditory fear conditioning, BDNF infused into the IL mPFC reduced conditioned fear for up to 48 hours, even in the absence of extinction training, which suggests that BDNF substituted for extinction. Similar to extinction, BDNF-induced reduction in fear required N-methyl-D-aspartate receptors and did not erase the original fear memory. Rats failing to learn extinction showed reduced BDNF in hippocampal inputs to the IL mPFC, and augmenting BDNF in this pathway prevented extinction failure. Hence, boosting BDNF activity in hippocampal-infralimbic circuits may ameliorate disorders of learned fear.